A milder form of molybdenum cofactor deficiency type A presenting as Leigh's syndrome-like phenotype highlighting the secondary mitochondrial dysfunction: a case report - Almudhry, Montaha; Prasad, Asuri N.; Rupar, C. Anthony; Tay, Keng Yeow; Ratko, Suzanne; Jenkins, Mary E.; Prasad, Chitra (Frontiers in Neurology, 2023)
Background Molybdenum cofactor deficiency (MoCD) (OMIM# 252150) is an autosomal-recessive disorder caused by mutations in four genes involved in the molybdenum cofactor (MOCO) biosynthesis pathway. Objectives We report a milder phenotype in a patient with MOCS1 gene mutation who presented with a Leigh-like presentation. Case report We present the case of a 10-year-old boy who was symptomatic at the age of 5 months with sudden onset of dyskinesia, nystagmus, and extrapyramidal signs following a febrile illness. Initial biochemical, radiological, and histopathological findings a Leigh syndrome-like phenotype; however, whole-exome sequencing detected compound heterozygous mutations in MOCS1 gene, c.1133 G>C and c.217C>T, confirming an underlying MoCD. This was biochemically supported by low uric acid level of 80 (110–282 mmol/L) and low cystine level of 0 (3–49), and a urine S-sulfocysteine at 116 (0–15) mmol/mol creatinine. The patient was administered methionine- and cystine-free formulas. The patient has remained stable, with residual intellectual, speech, and motor sequelae. Conclusion This presentation expands the phenotypic variability of late-onset MoCD A and highlights the role of secondary mitochondrial dysfunction in its pathogenesis.